HYMNÉ À LA BEAUTÉ KARYA CHARLES BAUDELAIRE: KAJIAN SEMIOTIKA PUISI RIFFATERRE - Sunahrowi Sunahrowi; Marita Restu N (Universitas Negeri Makassar, 2018)
Abstract. Hymné à la Beauté The work of Charles Baudelaire: The Semiotics Review of Riffaterre Poems. This study aims to reveal the hidden meaning of Hymne à la Beauté poem by using semiotic method. The method is designed with qualitative research descriptive analysis. The data are sourced from the work of Charles Baudelaire in the anthology of poetry Les fleurs du Mal. Data analysis was done by analytical descriptive method. The results show that the Hymne à la Beauté poem contains Baudelaire love strands to Jeanne Duval, which is represented through various expressions of poetry and expressionlessness. This poem shows the admiration of a man to a woman and also the despair of love.